Co-delivery of paclitaxel and doxorubicin using polypeptide-engineered nanogels for combination therapy of tumor. (19th January 2022) - Yang, Jie; Jin, Rui-Mei; Wang, Shen-Yan; Xie, Xiao-Ting; Hu, Wei; Tang, Hong-Feng; Liu, Bo
Abstract: Loading of chemotherapeutic agents into nanoparticles has been demonstrated to be an effective strategy for cancer therapy. However, simultaneous delivery of different functional drugs to tumor sites for chemotherapy still remains challenging. In this study, nanogels formed by an engineered coiled-coil polypeptide PC10 A were designed and prepared as a carrier for co-delivery of paclitaxel (PTX) and doxorubicin (DOX) through ultrasonic treatment and electrostatic adsorption. The drug loading content and encapsulation efficiency of PTX and DOX in the PC10 A/PTX/DOX nanogels were 5.98 wt%, 70 wt%, and 8.55 wt%, 83 wt%, respectively. Because the polypeptide PC10 A was non-toxic and biodegradable, the PC10 A/PTX/DOX nanogels exhibited good biocompatibility. The in vitro and in vivo antitumor experiments showed that the PC10 A/PTX/DOX nanogels possessed obviously synergistic therapy effect of tumors and lower side effects compared with free PTX/DOX. Therefore, the PC10 A/PTX/DOX nanogels are promising to provide a new strategy for combination therapy of different functional drugs.